Fundamentals of Chinese culture - Liang, Shuming, 1893-1988, author. Link Link
1 online resource (416 pages)
Keywords: Chinese culture, to readers of English, is somewhat veiled in mystery. Fundamentals of Chinese Culture, a classic of great insight and profundity by noted Chinese thinker, educator and social reformist Liang Shuming, takes readers on an intellectual journey into the five-thousand-year-old culture of China, the world's oldest continuous civilization. With a set of Chinese-style cultural theories, the book well serves as a platform for Westerners' better understanding of the distinctive worldview of the Chinese people, who value family life and social stability, and for further mutual understanding and greater mutual consolidation among humanities scholars in different contexts, dismantling common misconceptions about China and bridging the gap between Chinese culture and Western culture. As a translation of Liang Shuming's original text, this book pulls back the curtain to reveal to Westerners a highly complex and nuanced picture of a fascinating people.